Filsafat Pendidikan Islam dan Relevansinya terhadap Pendidikan Islam Kontemporer: Penelitian - Andri Alipia; Dinda Siti Handayani; Dyah Islamika Mahdarani; Etika Pujianti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Islamic educational philosophy is a branch of philosophy that deeply examines the nature, goals, methods, and values ​​underlying education from an Islamic perspective. This philosophy is based on the Islamic outlook on life derived from the Qur'an, Hadith, and classical Islamic intellectual traditions, then contextualized with the challenges of the times. In the context of contemporary Islamic education, Islamic educational philosophy has a very important relevance. The modern world marked by globalization, technological developments, and socio-political dynamics requires Islamic education to be able to adapt without losing its identity. In the research conducted by the researcher this time, the approach used was a qualitative literature study approach. The research was carried out by collecting primary and secondary literature sources. While data classification is carried out from primary and secondary sources. Based on the results of the literature study, philosophizing means thinking more deeply, holistically, and systematically about various problems. Education can also be carried out in harmony with the philosophical approach, because philosophy can understand human experience as a whole.